REPRESENTASI BUDAYA JAWA DI ERA MODERN PADA FILM LOSMEN BU BROTO - Putri, Tiara Nabila Nugraha; Bernard Realino Danu Kritstianto (Jurnal Spektrum Komunikasi, 2025)
In modern dynamics, culture undergoes a significant transformation due to the influence of globalization and technology. Javanese culture as one of Indonesia's cultural heritage experiences challenges in maintaining identity in the midst of globalization. Film as a medium that has a wide and deep reach, has the potential to reflect culture and shape people's perceptions. The purpose of this study is for how Javanese culture is represented in contemporary artworks such as the film "Losmen Bu Broto" to be important to study. The film "Losmen Bu Broto" is an Indonesian film released in 2021. This film tells the story of a Javanese family who owns an inn called Losmen Bu Broto. The daily life of the Broto family in running its business there are problems that occur that make disputes. In this film is shown cultural symbols that are in harmony with modern life. This research method is a quasi-qualitative research method with John Fiske's semiotic research method. Semiotics is a method that studies a sign analyzed by Fiske's model, which uses 3 levels, namely reality, representation, and ideology. Researchers use a type of quasi-qualitative research to explain intensively and in detail the symptoms and social phenomena chosen by researchers, namely how Javanese culture adapts in the modern era through signs in films.